Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

The number [tex]$b$[/tex] varies directly with the number [tex]$a$[/tex]. For example, [tex]$b = 2 \frac{3}{4}$[/tex] when [tex][tex]$a = -2 \frac{3}{4}$[/tex][/tex]. Which equation represents this direct variation between [tex]$a$[/tex] and [tex]$b$[/tex]?

A. [tex]b = -a[/tex]

B. [tex]-b = -a[/tex]

C. [tex]b - a = 0[/tex]

D. [tex]b(-a) = 0[/tex]


Sagot :

To solve for the equation that represents the direct variation between [tex]\( a \)[/tex] and [tex]\( b \)[/tex], we are given that [tex]\( b \)[/tex] varies directly with [tex]\( a \)[/tex] and the specific values [tex]\( b = 2\frac{3}{4} \)[/tex] and [tex]\( a = -2\frac{3}{4} \)[/tex].

Let's break down what this means:

1. Understand the Relationship: In problems of direct variation, we typically know that [tex]\( b \)[/tex] varies directly with [tex]\( a \)[/tex]. This can be expressed as:
[tex]\[ b = k \cdot a \][/tex]
where [tex]\( k \)[/tex] is a constant of proportionality.

2. Substitute the Given Values: We substitute the given values into the equation to find [tex]\( k \)[/tex].
[tex]\[ b = 2\frac{3}{4} \quad \text{and} \quad a = -2\frac{3}{4} \][/tex]
Therefore,
[tex]\[ 2.75 = k \cdot (-2.75) \][/tex]

3. Solve for [tex]\( k \)[/tex]: To find [tex]\( k \)[/tex], we solve the equation:
[tex]\[ k = \frac{2.75}{-2.75} = -1 \][/tex]

4. Write the Equation: Now that we have determined [tex]\( k \)[/tex], we substitute it back into the direct variation equation:
[tex]\[ b = -1 \cdot a \][/tex]
Simplifying,
[tex]\[ b = -a \][/tex]

Therefore, the equation that represents this direct variation is:
[tex]\[ b = -a \][/tex]

To verify, here are the equations with reasons as to why they don't fit:
- [tex]\(\boldsymbol{-b=-a}\)[/tex]: This simplifies to [tex]\( b = a \)[/tex], which does not match the given values.
- [tex]\(\boldsymbol{b-a=0}\)[/tex]: This also simplifies to [tex]\( b = a \)[/tex], which again does not match the given values.
- [tex]\(\boldsymbol{b(-a)=0}\)[/tex]: This implies [tex]\( b=0 \)[/tex] or [tex]\( -a=0 \)[/tex], which is not relevant to the given values.

Hence, the correct representation is:
[tex]\(\boxed{b = -a}\)[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.